Nano-fiber composite hydrogel capable of removing active oxygen and promoting repair as well as preparation and application of nano-fiber composite hydrogel

By developing a composite hydrogel material, using crosslinking networks and design of loaded staple fibers and nanoenzymes, the shortcomings of existing methods for treating chronic wounds are solved, and the effect of reactive oxygen scavenging and promoting wound healing is achieved.

CN119770712APending Publication Date: 2025-04-08DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411985190.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing local nursing process for clinical treatment of chronic wounds is cumbersome, with low cure rate and high recurrence rate. The traditional dressing function is single, and it cannot meet the dynamic needs of the chronic wound healing process.

Method used

A composite hydrogel material, including a first cross-linking network and a second cross-linking network of sodium polyacrylate, is developed to interpenetrate and load staple fibers and nanoenzymes, form a stable structure through ultraviolet light irradiation, and realize reactive oxygen scavenging and pro-repair functions.

Benefits of technology

This hydrogel material can effectively remove reactive oxygen species, inhibit chronic wound inflammation, accelerate healing, and continuously promote wound tissue repair by slowly releasing pro-repair drugs to meet the healing needs at different stages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770712A_ABST
    Figure CN119770712A_ABST
Patent Text Reader

Abstract

The invention relates to nanofiber composite hydrogel capable of removing active oxygen and promoting repair as well as preparation and application of the nanofiber composite hydrogel. According to the nanofiber composite hydrogel, a phenylboronic acid group grafted with a natural polymer and a cis-diol-containing polymer form a first cross-linked network through a boric acid ester bond; after ultraviolet crosslinking, sodium acrylate forms a sodium polyacrylate network through free radical polymerization, the sodium polyacrylate network and the first crosslinking network interpenetrate, the two crosslinking networks enhance the mechanical and adhesive properties of the hydrogel through the synergistic effect, supported nano-enzyme is released to endow the hydrogel with the capacity of removing active oxygen and inhibiting inflammation, and meanwhile, the hydrogel has the function of inhibiting inflammation. The electrospun short fiber can continuously and slowly release the repair promoting medicine to accelerate the healing of chronic wounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of hydrogels, and particularly relates to a nanofiber composite hydrogel capable of removing active oxygen and promoting repair, and a preparation method and application thereof. Background Art

[0002] The local care process of conventional clinical treatment of chronic wounds is relatively cumbersome, including debridement, infection / inflammation control, and frequent changes of wound dressings. Although it can alleviate the condition and relieve the patient's pain to a certain extent, the overall cure rate is low and the recurrence rate is high. Traditional wound dressings such as gauze and film have a single function and cannot meet the dynamic needs of the entire chronic wound healing process. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a nanofiber composite hydrogel capable of removing active oxygen and promoting repair, and the preparation and application thereof.

[0004] The invention provides a composite hydrogel material, which comprises a first cross-linked network, a second cross-linked network of sodium polyacrylate and short fibers, wherein the first cross-linked network and the second cross-linked network of sodium polyacrylate are interpenetrating and load the short fibers; wherein the first cross-linked network is formed by boric acid groups grafted onto a natural polymer and a cis-diol-containing polymer through borate ester bonds.

[0005] The composite hydrogel material also includes nanoenzymes; the short fibers are drug-loaded short fibers, and further are drug-loaded aliphatic polyester polymer short fibers.

[0006] The present invention provides a method for preparing a composite hydrogel material, comprising:

[0007] (1) mixing short fibers, phenylboronic acid grafted natural polymer, sodium acrylate, a photoinitiator, N,N'-methylenebisacrylamide, and a solvent to obtain a first solution;

[0008] (2) mixing a cis-diol-containing polymer, a solvent, and a nanozyme to obtain a second solution;

[0009] (3) The first solution and the second solution are mixed and irradiated with ultraviolet light to obtain a composite hydrogel material.

[0010] Preferably, in step (1), phenylboronic acid is grafted onto a natural polymer, wherein the natural polymer comprises one or more of polylysine, gelatin, and hyaluronic acid.

[0011] The preparation method of the phenylboronic acid grafted natural polymer in step (1) comprises: mixing an aqueous solution of the natural polymer and a 4-formylphenylboronic acid solution, reacting at room temperature for 2 to 4 hours, slowly adding sodium cyanoborohydride and continuing the reaction for 16 to 24 hours, dialyzing after the reaction is completed, and freeze-drying to obtain the phenylboronic acid grafted natural polymer.

[0012] The mass volume ratio concentration of the aqueous solution of the natural polymer is 2-4% (w / v); the molar ratio of the 4-formylphenylboric acid, sodium cyanoborohydride and the natural polymer is (6-8):(6-8):1; the solvent of the 4-formylphenylboric acid solution includes one or more of methanol, ethanol and deionized water.

[0013] Preferably, the photoinitiator in step (1) includes one or both of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator I2959) and lithium phenyl-2,4,6-trimethylbenzoylphosphonate (photoinitiator LAP); and the solvent is one or both of water and glycerol.

[0014] Preferably, the short fibers in step (1) include drug-loaded aliphatic polyester polymer short fibers; the aliphatic polyester polymer includes one or more of polylactic acid-glycolic acid copolymer, polycaprolactone, and polylactic acid.

[0015] Furthermore, the preparation of the drug-loaded aliphatic polyester polymer staple fibers includes: mixing aliphatic polyester polymer materials, solvents, and drugs to obtain a spinning solution, electrospinning to obtain a nanofiber membrane, and then homogenizing the nanofiber membrane in tert-butanol, centrifugally washing, and freeze-drying to obtain aliphatic polyester polymer staple fibers.

[0016] Preferably, the concentration of the aliphatic polyester polymer material in the solvent is 0.15-0.25 g / mL; the drug is 5-15% of the mass of the aliphatic polyester polymer material; the drug includes one or more of deferoxamine mesylate, quercetin, asiatica glycoside, mangiferin, and nano zinc oxide; the solvent includes one or more of hexafluoroisopropanol, tetrahydrofuran, dichloromethane, and dimethyl sulfoxide.

[0017] The electrostatic spinning process includes: spinning voltage of 8-15 kV, perfusion speed of 0.5-2 mL / h, receiving distance of 10-20 cm, relative humidity of 20-60%, temperature of 20-50° C., and fiber receiving on glossy paper or aluminum foil.

[0018] The nanofiber membrane is homogenized in tert-butyl alcohol, washed by centrifugation, and freeze-dried: the speed of the homogenizer is 3000-10000 rpm, the homogenization time is 5-20 minutes, and the freeze-drying is performed by pre-cooling and freezing and then placing the membrane in a freeze dryer for more than 24 hours.

[0019] The nanofiber membrane and tert-butanol are mixed and homogenized with 300-500 mL of tert-butanol for each 3×3 cm nanofiber membrane.

[0020] Preferably, in step (1), the mass ratio of short fibers, phenylboronic acid grafted natural polymer, sodium acrylate and photoinitiator is (1-5): (2-5): (15-25): (0.6-1); the amount of N,N'-methylenebisacrylamide added is 1-3% of the molar amount of sodium acrylate.

[0021] Furthermore, the concentrations of the short fibers, phenylboronic acid grafted natural polymer, sodium acrylate and photoinitiator in the first solution are 1-3% (w / v), 3-6% (w / v), 10-30% (w / v) and 0.5-1% (w / v), respectively.

[0022] In the step (1), short fibers, phenylboronic acid grafted natural polymer, sodium acrylate, photoinitiator, N,N'-methylenebisacrylamide and solvent are mixed to obtain a first solution, specifically, sodium acrylate, photoinitiator and N,N'-methylenebisacrylamide are stirred and dissolved in the solvent at 55-65° C., and then the phenylboronic acid grafted natural polymer is added to dissolve, and after cooling, the short fibers are added at 25-37° C. to obtain the first solution.

[0023] Preferably, the cis-diol polymer in step (2) refers to a polymer in which two hydroxyl functional groups in the carbon chain present a cis-structure arrangement, and the cis-diol polymer includes one or more of polyvinyl alcohol, guar gum, and polydopamine; the solvent includes water; and the nanozyme includes at least one of nano manganese dioxide, nano cerium oxide, etc.;

[0024] Preferably, in the step (2), the concentrations of nanozymes and cis-diol-containing polymers in the second solution are 0.5-3% (w / v) and 6-12% (w / v), respectively; and the mass ratio of the phenylboronic acid grafted natural polymer to the cis-diol-containing polymer is 1:(1-2).

[0025] In the present invention, w / v in mass volume percentage is g / ml.

[0026] In the step (2), the cis-diol-containing polymer, solvent and nanozyme are mixed to obtain a second solution, which includes: uniformly dispersing the nanozyme in solvent water by ultrasound, and then adding the cis-diol-containing polymer and stirring and dissolving to obtain the second solution; wherein the ultrasound time is 10 to 30 minutes.

[0027] In the step (3), the volume ratio of the second solution to the first solution is (1-2):1.

[0028] Preferably, the ultraviolet light irradiation time in step (3) is 5 to 30 minutes, and further, the irradiation time under 365nm ultraviolet light is 5 to 30 minutes.

[0029] The present invention provides an application of the composite hydrogel material in the field of preparing chronic wound repair dressings.

[0030] In the present invention, the phenyl borate network and the polymer network are interpenetrated to form a reactive oxygen species (ROS) responsive hydrogel, which can respond to highly expressed ROS at the chronic wound and release nanoenzymes to clear it to inhibit inflammation, thereby accelerating the chronic wound to pass the inflammatory period. At the same time, the drug-loaded nanofibers inside the hydrogel slowly release the pro-repair drug to continuously promote wound tissue healing. The developed fiber composite hydrogel dressing can meet the dynamic needs of different stages of chronic wound healing to overcome the shortcomings of existing dressings in practical applications.

[0031] The present invention mixes electrospun short fibers loaded with pro-repair drugs, phenylboronic acid grafted natural polymers, sodium acrylate, photoinitiators and solvents, and then blends the obtained mixed solution with nanozymes and a mixed dispersion of cis-diol structured polymers to form a covalent network, and further irradiates the mixed solution with ultraviolet light to form an interpenetrating network nanofiber composite hydrogel with a stable structure. In the present invention, the phenylboronic acid groups grafted with the natural polymer and the cis-diol-containing polymer form a first cross-linked network through borate bonds, and after ultraviolet cross-linking, sodium acrylate forms a sodium polyacrylate network through free radical polymerization and interpenetrates with the first cross-linked network. The two cross-linked networks enhance the mechanical and adhesive properties of the hydrogel through synergistic effects, release the loaded nanozymes to give the hydrogel the ability to remove active oxygen and inhibit inflammation, and at the same time, the electrospun short fibers can continuously and slowly release the pro-repair drugs to accelerate the repair of chronic wounds.

[0032] Beneficial Effects

[0033] (1) The active oxygen scavenging and repair-promoting fiber composite hydrogel dressing prepared by the present invention is composed of a phenyl borate network formed by a natural polymer and a cis-diol-containing polymer, and an interpenetrating sodium acrylate polymerization network, and the mechanical properties are enhanced. When applied to wounds at joints, the dressing can be ensured to fit the wound joints.

[0034] (2) The active oxygen scavenging and repair-promoting fiber composite hydrogel dressing prepared by the present invention has good active oxygen scavenging performance to inhibit chronic wound inflammation and can achieve more than 90% of hydrogen peroxide removal within 60 minutes.

[0035] (3) The active oxygen scavenging and repair-promoting fiber composite hydrogel dressing prepared by the present invention can dynamically respond to the problems that need to be overcome at different stages of chronic wound healing due to the rapid release of nanozymes and the slow release of repair-promoting drugs. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic diagram of the preparation of the active oxygen scavenging and repair-promoting fiber composite hydrogel dressing of the present invention;

[0037] Figure 2 The nano short fibers are obtained after homogeneous dispersion in Example 1;

[0038] Figure 3 This is a photo of the in situ formed fiber composite hydrogel dressing in Example 1;

[0039] Figure 4 Compression stress-strain curves of the double-network cross-linked hydrogel in Example 1 and the phenyl borate cross-linked hydrogel in Example 2;

[0040] Figure 5 is the adhesion strength-displacement curve of the double-network cross-linked network hydrogel in Example 1;

[0041] Figure 6 is the hydrogen peroxide removal performance of the hydrogel dressing, wherein a is the hydrogel dressing without additives in Example 3, b is the hydrogel dressing loaded with nano cerium oxide in Example 1, and c is the hydrogel dressing loaded with nano manganese dioxide in Example 4. DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0043] Polylactic acid-glycolic acid copolymer, with a ratio of lactic acid to glycolic acid of 75:25, was purchased from Jinan Daigang Biomaterial Co., Ltd.; quercetin; hexafluoroisopropanol with a specification of 99.5%, was purchased from Shanghai McLean Biochemical Technology Co., Ltd.; tert-butyl alcohol with a specification of AR, ≥99.5%, was purchased from Shanghai Titan Chemical Co., Ltd.; polylysine with a molecular weight of 3800-4200, was purchased from Beijing Inokai Technology Co., Ltd. (Shanghai); 4-formylphenylboronic acid with a specification of RG, 97%, was purchased from Shanghai Titan Chemical Co., Ltd.; sodium cyanoborohydride with a specification of 98%, was purchased from Shanghai Haohong Biomedical Technology Co., Ltd.; ethanol with a specification of 99.8%, Purchased from Shanghai McLean Biochemical Technology Co., Ltd.; sodium acrylate specification is RG, 98%, purchased from Shanghai Titan Chemical Co., Ltd.; N, N-dimethylformamide specification is AR, ≥99.5% (GC), purchased from Shanghai Titan Chemical Co., Ltd.; photoinitiator I2959 specification is 98.0%, purchased from Shanghai Ron Reagent Co., Ltd.; polyvinyl alcohol specification is Mw~47,000, purchased from Shanghai McLean Biochemical Technology Co., Ltd.; nano cerium oxide specification is 20nm~50nm, 99.5%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; nano manganese dioxide specification is AR, 100nm, purchased from Shanghai McLean Biochemical Technology Co., Ltd.

[0044] Preparation method of phenylboronic acid grafted polylysine: 2.65g 4-formylphenylboronic acid is dissolved in 80mL ethanol, 4g polylysine is dissolved in 80mL deionized water at room temperature, then the polylysine aqueous solution is added to the ethanol solution containing 4-formylphenylboronic acid to react for 4h, 1.11g sodium cyanoborohydride is slowly added and the reaction is continued for 18h. Subsequently, the mixture is dialyzed in deionized water for 5 days, and phenylboronic acid grafted polylysine is obtained after freeze drying.

[0045] Test method:

[0046] Antioxidant performance test: Prepare nanofiber composite hydrogel, mix 1.2g hydrogel dressing sample with 10mL1mM hydrogen peroxide solution, incubate at 37℃ for 60min, take 1mL supernatant and 2mL Ti(SO4)2 solution (1.33mL 24% Ti(SO4)2 and 8.33mLH2SO4 dissolved in 50mL deionized water) for 30min, and use UV spectrophotometer U-T9S to measure the data at a wavelength of 405nm.

[0047] Example 1

[0048] The preparation method of the nanofiber composite hydrogel dressing for removing active oxygen and promoting repair comprises the following steps:

[0049] (1) 2 g of PLGA was dissolved in 10 mL of hexafluoroisopropanol solution, and then 0.16 g of nano zinc oxide was added and stirred and ultrasonically dispersed to obtain a spinning solution;

[0050] (2) placing the spinning solution prepared in (1) into a 10 mL syringe, preparing a nanofiber membrane by electrospinning, and receiving the fiber membrane by a receiving substrate (glossy paper), wherein the electrospinning process parameters are: temperature 25±3°C, relative humidity 50±5%, spinning voltage 10 kV, and receiving distance 15 cm;

[0051] (3) The fiber membrane of (2) was cut into blocks of about 3×3 cm, and added to a homogenizer together with 300 mL of tert-butyl alcohol solution for homogenization. The homogenization process parameters were: speed 10000 rpm, time 15 min, the homogenate was centrifuged and washed twice with deionized water, and freeze-dried for 24 h to obtain drug-loaded nanofibers, such as Figure 2 shown.

[0052] (4) At 65°C, 1 g of sodium acrylate, 0.03 g of photoinitiator I2959, and 0.016 g of N,N'-methylenebisacrylamide were stirred and dissolved in 5 mL of solvent (the volume ratio of glycerol to water was 2:3), and then 0.2 g of phenylboronic acid grafted polylysine was added and continued to dissolve at the same temperature for 1 hour. After the solution was cooled, 0.05 g of the short fiber prepared in (3) was added at 37°C to obtain solution 1; 0.5 g of polyvinyl alcohol was dissolved in 5 mL of deionized water, and then 0.025 g of nano-cerium oxide was added, stirred and dispersed, and further, ultrasonicated by an ultrasonic cleaner to make it uniformly dispersed to obtain solution 2;

[0053] (5) using a disposable medical syringe, successively injecting solution 1 and solution 2 into the mold, with the injection amount ratio being 1:1;

[0054] (6) The hydrogel in (5) was irradiated with 365 nm ultraviolet light for 10 min to form an interpenetrating hydrogel of a sodium acrylate polymer network and a phenyl borate network; the actual photo of the in situ formed nanofiber composite hydrogel dressing is shown in FIG. Figure 3 shown.

[0055] A polytetrafluoroethylene plate with a hole diameter and depth of 1 cm was used as a hydrogel receiving vessel, 1 mL of the solution in step (5) (the sum of solution 1 and solution 2) was added dropwise, irradiated with 365 nm ultraviolet light for 10 min, and tested by applying a pressure of 30 N and a uniform compression speed of 10 mm / min using an electronic universal testing machine. Figure 4 The figure shows the compressive stress-strain curve of the hydrogel. When the compression deformation of the double network interpenetrating hydrogel is 80%, the maximum compressive stress is 62.44 kPa.

[0056] Pigskin was used as a biological tissue model to test the tissue adhesion performance of the hydrogel through a lap shear test. First, the pigskin was cut into rectangular slices (50 mm long x 20 mm wide), and then 500 μL of the solution in step (5) (the sum of solution 1 and solution 2) was dripped onto the surface, irradiated with 365 nm ultraviolet light for 10 min, and then another piece of pigskin was placed on the hydrogel, with a bonding area of ​​20 mm × 20 mm. The lap shear test was conducted by applying a 30 N tensile force at a uniform rate using an electronic universal testing machine. Figure 5 The figure shows the adhesion strength-displacement curve of the adhesion performance test experiment, and the maximum adhesion strength is 17.12 kPa.

[0057] Active oxygen scavenging properties such as Figure 6 As shown, 71.6% of hydrogen peroxide can be removed within 60 minutes.

[0058] Example 2

[0059] The preparation method of the nanofiber composite hydrogel dressing for removing active oxygen and promoting repair comprises the following steps:

[0060] (1) 2 g of PLGA was dissolved in 10 mL of hexafluoroisopropanol solution, and then 0.16 g of nano zinc oxide was added and stirred and ultrasonically dispersed to obtain a spinning solution;

[0061] (2) placing the spinning solution prepared in (1) into a 10 mL syringe, preparing a nanofiber membrane by electrospinning, and receiving the fiber membrane by a receiving substrate (glossy paper), wherein the electrospinning process parameters are: temperature 25±3°C, relative humidity 50±5%, spinning voltage 10 kV, and receiving distance 15 cm;

[0062] (3) The fiber membrane of (2) was cut into blocks of approximately 3×3 cm and added to a homogenizer together with 300 mL of tert-butyl alcohol solution for homogenization. The homogenization process parameters were: speed 10,000 rpm, time 15 min. The homogenate was centrifuged and washed twice with deionized water, and freeze-dried for 24 h to obtain drug-loaded nanofibers.

[0063] (4) At 65°C, 1 g of sodium acrylate, 0.03 g of photoinitiator I2959, and 0.016 g of N,N'-methylenebisacrylamide were stirred and dissolved in 5 mL of solvent (the volume ratio of glycerol to water was 2:3), and then 0.2 g of phenylboronic acid grafted polylysine was added and continued to dissolve at the same temperature for 1 hour. After the solution was cooled, 0.05 g of the short fiber prepared in (3) was added at 37°C to obtain solution 1; 0.5 g of polyvinyl alcohol was dissolved in 5 mL of deionized water, and then 0.025 g of nano-cerium oxide was added, stirred and dispersed, and further, ultrasonicated by an ultrasonic cleaner to make it uniformly dispersed to obtain solution 2;

[0064] (5) Solution 1 and solution 2 are injected into the mold in sequence through a disposable medical syringe at an injection ratio of 1:1, and are gently stirred to mix them evenly to obtain a phenylboronic acid ester network cross-linked hydrogel.

[0065] A polytetrafluoroethylene plate with a hole diameter and depth of 1 cm was used as a hydrogel receiving vessel, and 1 mL of the solution of step (5) (the sum of solution 1 and solution 2) was added dropwise to form a phenyl borate network cross-linked hydrogel. An electronic universal testing machine was used to apply a pressure of 30 N and a uniform compression speed of 10 mm / min for testing. When the compression deformation was 80%, the maximum compressive stress was 19.05 kPa.

[0066] Example 3

[0067] The preparation method of the nanofiber composite hydrogel dressing is the same as that of Example 1, except that nano cerium oxide is not added.

[0068] Example 4

[0069] The preparation method of the nanofiber composite hydrogel dressing is the same as that of Example 1, except that the nanoenzyme in step (4) is nanomanganese dioxide. In the active oxygen scavenging performance test, 98.9% of hydrogen peroxide can be removed within 60 minutes.

Claims

1. A composite hydrogel material, characterized in that: The composite hydrogel material comprises a first cross-linked network, a second cross-linked network of sodium polyacrylate and short fibers, and the first cross-linked network and the second cross-linked network of sodium polyacrylate are interpenetrating and load the short fibers; wherein the first cross-linked network is formed by boric acid groups grafted onto a natural polymer and a cis-diol-containing polymer through borate ester bonds.

2. The composite hydrogel material according to claim 1, characterized in that: The composite hydrogel material also includes nanoenzymes; the short fibers are drug-loaded short fibers.

3. A method for preparing a composite hydrogel material, comprising: (1) mixing short fibers, phenylboronic acid grafted natural polymer, sodium acrylate, a photoinitiator, N,N'-methylenebisacrylamide, and a solvent to obtain a first solution; (2) mixing a cis-diol-containing polymer, a solvent, and a nanozyme to obtain a second solution; (3) The first solution and the second solution are mixed and irradiated with ultraviolet light to obtain a composite hydrogel material.

4. The preparation method according to claim 3, characterized in that: In step (1), the short fibers include drug-loaded aliphatic polyester polymer short fibers; the aliphatic polyester polymer includes one or more of polylactic acid-glycolic acid copolymer, polycaprolactone, and polylactic acid; In the step (1), phenylboronic acid is grafted onto a natural polymer, wherein the natural polymer comprises one or more of polylysine, gelatin, and hyaluronic acid; In the step (1), the photoinitiator includes one or both of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone and lithium phenyl-2,4,6-trimethylbenzoylphosphonate; and the solvent includes one or both of water and glycerol.

5. The preparation method according to claim 4, characterized in that: The preparation of the drug-loaded aliphatic polyester polymer short fibers comprises: mixing aliphatic polyester polymer materials, solvents, and drugs to obtain spinning solution, electrospinning to obtain nanofiber membranes, and then homogenizing the nanofiber membranes in tert-butyl alcohol, centrifugally washing, and freeze-drying to obtain aliphatic polyester polymer short fibers.

6. The preparation method according to claim 5, characterized in that: The concentration of the aliphatic polyester polymer material in the solvent is 0.15-0.25 g / mL; the drug is 5-15% of the mass of the aliphatic polyester polymer material; the drug includes one or more of deferoxamine mesylate, quercetin, asiatica glycoside, mangiferin, and nano zinc oxide; and the solvent includes one or more of hexafluoroisopropanol, tetrahydrofuran, dichloromethane, and dimethyl sulfoxide.

7. The preparation method according to claim 3, characterized in that: In the step (1), the mass ratio of the short fiber, the phenylboronic acid grafted natural polymer, the sodium acrylate and the photoinitiator is (1-5): (2-5): (15-25): (0.6-1); the amount of N,N'-methylenebisacrylamide added is 1-3% of the molar amount of the sodium acrylate.

8. The preparation method according to claim 3, characterized in that: The cis-diol polymer in step (2) includes one or more of polyvinyl alcohol, guar gum, and polydopamine; the solvent includes water; the nanozyme includes at least one of nano manganese dioxide, nano cerium oxide, etc.; The ultraviolet light irradiation time in step (3) is 5 to 30 minutes.

9. The preparation method according to claim 3, characterized in that: In the step (2), the concentrations of nanozymes and cis-diol-containing polymers in the second solution are 0.5-3% (w / v) and 6-12% (w / v), respectively; the mass ratio of the phenylboronic acid grafted natural polymer to the cis-diol-containing polymer is 1:(1-2).

10. Use of the composite hydrogel material according to claim 1 in the preparation of chronic wound repair dressings.